THE CHILD RIGHTS IN ISLAMIC LAW WITH A SPECIAL FOCUS ON ACEH - A.Hamid Sarong; Nur Ahmad Fadhil Lubis (LKKI Fakultas Syariah dan Hukum Universitas Islam Negeri Ar-Raniry, 2019)
Child rights has become global concern, indicated from several law instruments which legislated by several countries in the world. In international context, United Nations has created several laws, including protocols and resolutions to protect rights of children. Those laws have consisted of soft-law which sometimes having no hard sanctions. In Indonesian context, there are a number of law instruments protecting child rights such as Law of Child Protection. However, the Law have not fully covered the implementation of Islamic law in Aceh. A number of Qanun (bylaws) in Aceh have not specifically protected child rights. There are still a lot of norms in Islamic criminal law not defining child rights. In Islamic law, Al-Quran and the Prophet Muhammad PBUH have paid serious attention on children rights. Islamic law has given greatest care to safeguarding all that is needed to guarantee a wholesome psychological climate for the rearing of children, an environment wherein they learn about the world formulate their norms and behaviour. Abstrak: Hak-hak anak telah menjadi perhatian global, sebagaimana ditunjukkan oleh instrumen-instrumen hukum yang telah disahkan di beberapa negara di dunia. Dalam konteks internasional, PBB telah menciptakan beberapa undang-undang, termasuk protokol dan resolusi untuk melindungi hak-hak anak. Undang-undang tersebut terdiri dari hukum lunak, yang terkadang tidak memiliki sanksi berat. Dalam konteks Indonesia, terdapat beberapa instrumen hukum yang melindungi hak-hak anak, contohnya: Hukum Perlindungan Anak. Namun, Undang-undang (UU) tersebut belum sepenuhnya mencakup pelaksanaan hukum Islam di Aceh. Beberapa Qanun di Aceh belum secara khusus melindungi hak-hak anak. Selain itu, masih banyak norma dalam hukum pidana Islam yang tidak mendefinisikan hak anak. Dalam hukum Islam, Al-Quran dan Nabi Muhammad SAW telah memberikan perhatian serius terhadap hak-hak anak. Hukum Islam telah memberikan perhatian besar untuk melindungi semua yang memerlukan perlindungan, demi menjamin iklim psikologis yang sehat untuk membesarkan anak-anak di lingkungan di mana mereka belajar tentang dunia yang merumuskan norma dan perilaku mereka. Kata kunci: Hak Anak, Hukum Islam, Hukum Islam di Aceh